Shocks de precios externos y su impacto en el consumo y en la inversión: Alguna evidencia para Argentina - Luis N. Lanteri (Atlantic Review of Economics, 2017)
– This paper investigates the impact of external price shocks on private consumption and investment and the sources of fluctuations in these variables, in the case of Argentina, employing structural VEC models (Structural Vector Error Correction) and quarterly data, covering the period 1993Q1-2017Q1. To that end, short and long-terms restrictions are imposed and five structural shocks are identified: terms of trade, consumption, investment, real exchange rate and unemployment rates. The results show, that both consumption and investment, respond positively and permanently to the external price shocks and are influenced positively each other: investment has a positive effect on private consumption and total consumption impacts on investment positively. A real exchange rate depreciated would have a negative effect on private consumption and investment, in the short term.
Keywords: C3; F41; 330; terms of trade; consumption; investment; SVEC models; Argentina